Produção de páginas jornalísticas dinâmicas direto na nuvem, com hipertextos, multimidia e textmining, multiplataforma, multidevices, utilizando paradigma funcional LISP com EMACS ORG-MODE - Lima, Tatiana Oliveira (2016)
We're in the Information Age, where anyone with a smarthphone it’s capable to covers a moment, register and publish it on the internet. This creates a serious problem to newspapers: when the news go to air, are already old. This paper presents an overview of the situation of press and digital journals in the country, and proposes an efficient solution to enable the journalist to produce dynamic news pages directly in the cloud, with hypertext, multimedia and textmining, multiplatform, multidevices, using functional paradigm with emacs org -mode, e-lisp.